Religion and the Everyday Life of Manichaeans in Kellis : Beyond Light and Darkness - Brand, Mattias, (Nag Hammadi and Manichaean Studies ;, 2022)
Religion is never simply there . In Religion and the Everyday Life of Manichaeans in Kellis , Mattias Brand shows where and when ordinary individuals and families in Egypt practiced a Manichaean way of life. Rather than portraying this ancient religion as a well-structured, totalizing community, the fourth-century papyri sketch a dynamic image of lived religious practice, with all the contradictions, fuzzy boundaries, and limitations of everyday life. Following these microhistorical insights, this book demonstrates how family life, gift-giving, death rituals, communal gatherings, and book writing are connected to our larger academic debates about religious change in late antiquity.